2021
DOI: 10.1186/s42077-021-00170-6
|View full text |Cite
|
Sign up to set email alerts
|

Opioid-free general anaesthesia for transthoracic oesophagectomy: does it improve postoperative analgesia and other recovery criteria? A prospective randomised study

Abstract: Background Side effects related to intraoperative opioid administration are well known. Recently, it was found that opioids may inhibit cellular immunity through their effects on natural killer cell activity, stimulate angiogenesis and accentuate cancer cell growth. Hence, peri-operative use of opioids might affect long-term oncological outcomes in cancer surgical patients. Opioid-free anaesthesia (OFA) is a methodology that dodges narcotic use during anaesthesia by using blends of several drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Opioid-free anesthesia (OFA) is a multimode anesthesia strategy that combines multiple nonopioid drugs and/or techniques to obtain high-quality anesthesia and has recently gained increasing attention [ 4 ]. The impact of OFA has been investigated in the case of transthoracic oesophagectomy in comparison with opioid-based anesthesia technique (OBA) on postoperative analgesia and recovery criteria (hemodynamics, respiratory rate, and hemoglobin oxygen saturation) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Opioid-free anesthesia (OFA) is a multimode anesthesia strategy that combines multiple nonopioid drugs and/or techniques to obtain high-quality anesthesia and has recently gained increasing attention [ 4 ]. The impact of OFA has been investigated in the case of transthoracic oesophagectomy in comparison with opioid-based anesthesia technique (OBA) on postoperative analgesia and recovery criteria (hemodynamics, respiratory rate, and hemoglobin oxygen saturation) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study done by Abdelrahman and Algharabawy. 17 showed that there were statistically significant lower values in opioid based anesthesia group than opioid free anesthesia at 20 min, 30 min post extubation and at the first and second hours postoperatively. But this difference was insignificant immediately and after 10 min post extubation, third, Our study showed that the incidence of vomiting was higher in the Group OP with significant difference than the Group KD.…”
Section: Discussionmentioning
confidence: 89%